Unraveling Subcellular and Ultrastructural Changes During Vitrification of Human Spermatozoa: Effect of a Mitochondria-Targeted Antioxidant and a Permeable Cryoprotectant - Kumar, Pradeep; Wang, Mengying; Isachenko, Evgenia; Rahimi, Gohar; Mallmann, Peter; Wang, Wanxue; Brandenstein, Melanie von; Isachenko, Vladimir (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria-targeted antioxidants have great potential to counterbalance the generated reactive oxygen species (ROS) because they cross the inner membrane of the mitochondria. Still, their use was not reported in vitrified human spermatozoa. Our laboratory has successfully vitrified spermatozoa without the use of permeable cryoprotectants, but subcellular-level evidence was missing. Therefore, this study aimed to improve spermatozoa vitrification using a mitochondria-targeted antioxidant (mitoquinone, MitoQ), reveal ultrastructural changes in the spermatozoa due to the use of a permeable cryoprotectant, and report alterations of functional proteins during the spermatozoa vitrification process. For this, each of 20 swim-up-prepared ejaculates was divided into seven aliquots and diluted with a vitrification medium supplemented with varying concentrations of MitoQ (0.02 and 0.2 μM), glycerol (1, 4, and 6%), and a combination of MitoQ and glycerol. All aliquots were vitrified by the aseptic capillary method developed in our laboratory. The spermatozoa function assays revealed that the addition of either MitoQ (0.02 μM), glycerol (1%), or a combination of MitoQ (0.02 μM) and glycerol (1%) in the vitrification medium results in better or equivalent spermatozoa quality relative to the control. Transmission electron microscopy revealed that MitoQ protects the spermatozoa from undergoing ultrastructural alterations, but glycerol induced ultrastructural alterations during the vitrification process. Next, we performed label-free quantitative proteomics and identified 1,759 proteins, of which 69, 60, 90, and 81 were altered in the basal medium, 0.02 μM MitoQ, 1% glycerol, and Mito-glycerol groups, respectively. Actin, tubulins, and outer dense fiber proteins were not affected during the vitrification process. Some of the identified ubiquitinating enzymes were affected during spermatozoa vitrification. Only a few proteins responsible for phosphorylation were altered during vitrification. Similarly, several proteins involved in spermatozoa–egg fusion and fertilization (IZUMO1 and Tektin) were not affected during the vitrification process. In conclusion, MitoQ attenuates the vitrification-induced ultrastructural changes and alterations in the key proteins involved in spermatozoa functions and fertilization.